Elaboração e caracterização de filmes biodegradáveis de blendas poliméricas de amido de lírio-do-brejo (Hedychium coronárium) e amido do fruto-do-lobo (Solanum lycorcarpum st. Hill) - (:unkn) unknown (Universidade Estadual de Goiás, 2009)
The plastics industry for a long time sought to develop materials that were more durable and resistant to possess high life in packaging in general. But with time were emerging concerns about the environment, depending on the disposal of materials that generate large accumulation of trash. The synthetic polymer takes on average 150 years to degrade. Some time environmentalists and scientists are developing research that focus on the replacement of conventional plastics by biodegradable plastics and photodegradable. Thus, a new technology is revolutionizing the market for disposables: is the thermoplastic starch, a biodegradable film produced from starch. The starch is a raw material in abundance, cheap and come from various sources. In the present study is the characteristics of two sources of starch little explored Goias’s Cerrado: starch fruit-of-wolf (AFL) and starch of lily-of-swamp (ALB), and later produced films and subsequently produced is biodegradable films with these starches, isolated or associated, with the addition of glycerol, which acted as a plasticizer. These biodegradable films produced were analyzed according to their thickness, solubility in water and permeability to water vapor, in addition to their mechanical behavior, and their thermal degradation. The starch present chemical composition, size, shape and temperature of the granules of impaste different. The biodegradable films showed thickness varied due to the casting process of preparation and concentration of glycerol, the solubility in water and permeability to water vapor (Paw) were higher as it increased the glycerol. The films of low, medium and high (Paw) were selected for mechanical analysis, thermal and degradation. Also observed the effect of glycerol on the mechanical properties, a decrease of tension in MPa and increasing the strain in percentage of biodegradable films made according to the increasing concentration of glycerol. The biodegradation of films using the Sturm test, occurred in approximately 7 days under the conditions examined, with the presence of high humidity and humus. It was found that in general the type of starch (AFL and ALB) did not influence both the characteristics of the films analyzed, but the concentration of glycerol.
Keywords: Hedychium coronarium; Solanum lycocarpum; Plastificante; Blendas poliméricas; Hedychium coronarium; Solanum lycocarpum; Plasticizer; Polymer blends; CIENCIAS EXATAS E DA TERRA::QUIMICA